Dinamika Kesenian Sasapian: Dari Tradisi Ritual hingga Media Promosi Pariwisata (1999-2017) - Elvira Mela Maudina; Saripudin Didin (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2021)
This research was written to answer the main problems related to how the dynamics of sasapian art occurred in 1999-2017. This research uses historical methods, consisting of several research steps. First, heuristics( collection of sources), criticisms, and most recent historiography (historical writing). From the research conducted, the results obtained that the appearance of sasapian art in Cihideung Village is backgrounded by the socio-cultural condition of cihideung village people who are very attached to magical life. This sasapian art first appeared between 1920-1940s, when sasapian art was considered as a means of communication between the people and the spirits of ancestors / karuhun, as well as as a form of gratitude to the Creator for abundant crops, and the availability of abundant water. Sasapian art continues to be traditionalized at Hajat cai/Ngaruat Solokan. In 1999, tourism developed in Cihideung Village, a tradition of Hajat cai/Ngaruat Solokan that displays sasapian art slowly began to be abandoned. Sasapian art began to reform as a means of people's entertainment. In 2007, sasapian art innovation was introduced under the name Sapi Gumarang, and created a tourism event called Cihideung Festival, since then sasapian arts changed function as a means of promoting tourism, which supports the implementation of creative economy in Cihideung Village. Factors that influence the dynamics that occur in Cihideung Village are globalization, tourism rate, and artist creativity.